Long-Term Clinical and Immunological Effects of Repeated Mesenchymal Stem Cell Injections in Patients With Progressive Forms of Multiple Sclerosis - Petrou, Panayiota; Kassis, Ibrahim; Ginzberg, Ariel; Halimi, Michel; Yaghmour, Nour; Abramsky, Oded; Karussis, Dimitrios (Frontiers in Neurology, 2021)
Background: Mesenchymal stem cells (MSC) were shown to possess immunomodulatory and neurotrophic effects. Our previous trials, have shown that intrathecal (IT) and intravenous (IV) administration of MSCs were safe and provided indications of beneficial clinical effects. Methods: This is an open prospective study to evaluate the safety and the long-term clinical and immunological effects of multiple injections of autologous MSCs in 24 patients with active-progressive MS. At inclusion, the mean age of the patients was 47.0 ± 9.22, and the mean EDSS score was 6.75 ± 0.68 (range: 5.5–7.5). Patients were initially treated with 1 ×106 MSCS/kg of body weight (IT + IV) and subsequently with up to additional eight courses of MSCs, at intervals of 6–12 months. The duration of the trial was 4 years. Results: No serious, treatment-related adverse events were observed during the follow-up period. Twenty-two of the 24 patients were either stable or improved at the last follow-up visit. Ten patients had a lower than baseline EDSS at the last follow-up (nine were among those who received >2 treatments and one in the subgroup of ≤ 2 treatments, p = 0.04). The mean EDSS score reduced from 6.75 ± 0.68 at baseline to 6.42 ± 0.84 at the last visit, during a median follow-up period of 27.8 months (p = 0.028). Immunological follow-up showed a transient upregulation of CD4+CD25+FoxP3+ cells and downregulation of the proliferative ability of lymphocytes. Conclusions: Repeated MSC treatments in patients with progressive MS were shown safe at the short/intermediate term and induced clinical benefits (especially in patients treated with >2 injections) that lasted for up to 4 years, paralleled by short-term immunomodulatory effects. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT04823000.